Entrepreneurial business start-ups and entrepreneurial failure: How to stand up after a fall? - Pan, Lee-Yun; Tsai, I-Chih; Popan, Shu-Hui; Chang, Shih-Chi (Frontiers in Psychology, 2022)
There are many reasons for entrepreneurs to start a business, but there is only a thin line between success and failure, and not everyone is willing to try to start a business again after encountering a failure. Therefore, it is worth exploring how start-up losers accumulate the energy of entrepreneurship and the reasons for starting a business again. In this study, the typical sampling method was adopted to select a suitable and representative case company entrepreneur for an in-depth interview. The results of this study revealed that in the process of the Entrepreneur starting a business three times, the Entrepreneur’s personal motivation and learning ability in the face of failure, coupled with family support, made the Entrepreneur willing to keep trying, even though he had to face the risk of repeated entrepreneurial failures, so that he could keep his positive energy on his entrepreneurial journey and eventually achieve a successful outcome.